Biological and probiotic characterization of spontaneous phage-resistant mutants of Lactobacillus plantarum - Briggiler Marcó, Mariángeles (2014)
Four spontaneous phage-resistant mutants, previously isolated from Lactobacillus plantarum ATCC 8014 using a phage cocktail (ATCC 8014-B1 and ATCC 8014-B2), were characterized about their probiotic potential. Phage-resistant mutants exhibited, in general, the same properties as those found for Lb. plantarum ATCC 8014 strain. However, mutant M1 evidenced a remarkably high resistance to gastrointestinal passage. Low values of either B-galactosidase activity or hydrophobicity were observed. Antimicrobial activity against Gram-negative and Gram-positive bacteria was evidenced and lactulose was the most fermented carbohydrate. Strains were sensitive to gentamicin, erythromycin, ampicillin and chloramphenicol, whereas production of biogenic amines was not observed. Finally, a selected phage-resistant mutant (M1) produced the same immunological response as the sensitive strain in mice fed for 10 consecutive days. These natural mutants, with similar or improved potentially probiotic characteristics regarding their sensitive strain, could be used during fermented food manufacture to minimize the phage attacks.